Insulin-like growth factor-1 stimulates retinal cell proliferation via activation of multiple signaling pathways - Camila Saggioro de Figueiredo; Ícaro Raony; Simone Vidal Medina; Eliezer de Mello Silva; Aline Araujo dos Santos; Elizabeth Giestal-de-Araujo (Current Research in Neurobiology, 2023)
Insulin-like growth factor-1 (IGF-1) plays critical roles in the development of the central nervous system (CNS), including the retina, regulating cell proliferation, differentiation, and survival. Here, we investigated the role of IGF-1 on retinal cell proliferation using primary cultures from rat neural retina. Our data show that IGF-1 stimulates retinal cell proliferation and regulates the expression of neurotrophic factors, such as interleukin-4 and brain-derived neurotrophic factor. In addition, our results indicates that IGF-1-induced retinal cell proliferation requires activation of multiple signaling pathways, including phosphatidylinositol 3-kinase, protein kinase Src, phospholipase-C, protein kinase C delta, and mitogen-activated protein kinase pathways. We further show that activation of matrix metalloproteinases and epidermal growth factor receptor is also necessary for IGF-1 enhancing retinal cell proliferation. Overall, these results unveil potential mechanisms by which IGF-1 ensures retinal cell proliferation and support the notion that manipulation of IGF-1 signaling may be beneficial in CNS disorders associated with abnormal cell proliferation.